PELATIHAN PEMBUATAN ALAT PENANGKAPAN IKAN RAMAH LINGKUNGAN - Mustasim Mustasim; Endang Gunaisah; Muhammad Ali Ulat; Handayani Handayani; Ismail Ismail; Amir M Suruwaky; Misbah Sururi; Vicky Rizky Affandy Katili; Hendra Poltak (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
Destructive fishing has the potential to reduce the sustainability of marine resources and the productivity of marine products which will have an impact on the welfare of fishermen. Various motives for destructive fishing include economic, social, cultural motives, and even ignorance that this action is against the law. Politeknik Kelautan dan Perikanan Sorong carries out community service as an effort to provide understanding regarding environmentally friendly fisheries through lectures and the practice of making environmentally friendly fishing gear. The activity lasted for 2 days, attended by 20 fishermen target partners of Saoka Village. The results of the practice in the form of environmentally friendly fishing gear are handed over to target partners for use in fishing operations.